APPLICATIONS WEBSITE DESIGN ON COUNTER HP VAN CELLULAR USING PHP AND ADOBE DREAMWEAVER CS3 - Irfan Fauzy; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Application website at Van Cellular counter is made to facilitate community in getting an update on developments surrounding the world of cell phones that are now increasingly popular in the community with ways to make the application a list of prices of mobile phones sold in one mobile counter, which is Mobile Van Cellular Conter who exactly was in the area are Pamulang Tangerang. Application of this website is made by using a merger between Adobe Dreamweaver CS3 software used to design web pages, programming language Hypertext Preprocessor (PHP) which is a server side scripting language for web content that integrates with the Hypertext Markup Language (HTML). In particular, PHP is designed to create dynamic web, which means that php can form a view based on current demand and is very easy to use and learn.